Extra virgin olive oil consumption reduces the risk of osteoporotic fractures in the PREDIMED trial. Issue 1 (February 2018) - García-Gavilán, J.F.; Bulló, M.; Canudas, S.; Martínez-González, M.A.; Estruch, R.; Giardina, S.; Fitó, M.; Corella, D.; Ros, E.; Salas-Salvadó, J.
Summary: Background & aims: The incidence of osteoporotic fractures is lower in countries in the Mediterranean basin. Virgin olive oil, a key component of the Mediterranean Diet (MDiet), with recognised beneficial effects on metabolism and cardiovascular health, may decrease the risk of osteoporotic fractures. The aim to this study was to explore the effect of chronic consumption of total olive oil and its varieties on the risk of osteoporosis-related fractures in a middle-aged and elderly Mediterranean population. Methods: We included all participants (n = 870) recruited in the Reus (Spain) centre of the PREvención con DIeta MEDiterránea (PREDIMED) trial. Individuals, aged 55–80 years at high cardiovascular risk, were randomized to a MedDiet supplemented with extra-virgin olive oil, a MedDiet supplemented with nuts, or a low-fat diet. The present analysis was an observational cohort study nested in the trial. A validated food frequency questionnaire was used to assess dietary habits and olive oil consumption. Information on total osteoporotic fractures was obtained from a systematic review of medical records. The association between yearly repeated measurements of olive oil consumption and fracture risk was assessed by multivariate Cox proportional hazards. Results: We documented 114 incident cases of osteoporosis-related fractures during a median follow-up of 8.9 years. Treatment allocation had no effect on fracture risk. Participants in the highest tertile of extra-virgin olive oil consumption had a 51% lower risk of fractures (HR:0.49; 95% CI:0.29–0.81. P for trend = 0.004) compared to those in the lowest tertile after adjusting for potential confounders. Total and common olive oil consumption was not associated with fracture risk. Conclusions: Higher consumption of extra-virgin olive oil is associated with a lower risk of osteoporosis-related fractures in middle-aged and elderly Mediterranean population at high cardiovascular risk.